Portugal in the 18th–20th centuries Russian poetry - Polina Poberezkina (Literatūra (Vilnius))
The article, which is the result of work on the self-titled anthology, examines one of the least studied areas of Russian poetic geography. The author explores the path from indirect reception through other European literatures to original lyrical travelogues and compares the image of Portugal in Soviet and émigré poetry. The main Portuguese loci and heroes of Russian poems, such as Lisbon, the Azores, L. de Camões, V. da Gama, F. Magellan, are analyzed.